How QFII Influence Chinese Stock Market Liberalization? Compare with Taiwan's Experience - Chan, Oi Yee, Iris (2008)
QFII (Qualified Foreign Institutional Investors) announced in November, 2002 and formally implemented in 1st of December, 2002. It is the initial stock market liberalization policy adopted by Chinese authorizes after the accession of WTO.